The Impact of Carbon Market and Carbon Tax on Green Growth Pathway in China: A Dynamic CGE Model Approach. Issue 6 (3rd May 2019) - Bi, Huimin; Xiao, Hao; Sun, Kejuan
ABSTRACT: Carbon market and carbon tax affect economic activity in various ways, resulting in different pathways for green growth in China. We build a dynamic computable general equilibrium (CGE) model to discuss the differences in green growth paths induced by differences in intrinsic technical incentives in carbon-abatement policies under three scenarios: a carbon market, a carbon tax, and a mixed policy. The main results are as follows. In carbon market scenario, although the short-term carbon mitigation effect is less prominent, the double dividend of emissions reduction and the gross domestic product (GDP) growth will come about in the long run according to the Porter hypothesis. Carbon tax leads to a relatively dramatic decrease in the growth of GDP and a positive effect on carbon mitigation in the short run; however, these effects decline in the long run. The effect of the mixed policy is not simple combination of the impacts of the above two policies, but shows another pathway for green growth.